Case Report: Durable therapy response to Osimertinib in rare EGFR Exon 18 mutated NSCLC - Cekay, Michael; Arndt, Philipp F.; Dumitrascu, Rio; Savai, Rajkumar; Braeuninger, Andreas; Gattenloehner, Stefan; Steiner, Dagmar; Roller, Fritz; Tello, Khodr; Hattar, Katja; Seeger, Werner; Sibelius, Ulf; et al. (Frontiers in Oncology, 2023)
Up to 20% of all non-small cell lung cancer patients harbor tumor specific driver mutations that are effectively treated with tyrosine kinase inhibitors. However, for the rare EGFR deletion-insertion mutation of exon 18, there is very little evidence regarding the effectiveness of tyrosine kinase inhibitors. A particular challenge for clinicians in applying tyrosine kinase inhibitors is not only diagnosing a mutation but also interpreting rare mutations with unclear therapeutic significance. Thus, we present the case of a 65-year-old Caucasian male lung adenocarcinoma patient with an EGFR Exon 18 p.Glu709_Thr710delinsAsp mutation of uncertain therapeutic relevance. This patient initially received two cycles of standard platinum-based chemotherapy without any therapeutic response. After administration of Osimertinib as second line therapy, the patient showed a lasting partial remission for 12 months. Therapy related toxicities were limited to mild thrombocytopenia, which ceased after dose reduction of Osimertinib. To our knowledge, this is the first report of effective treatment of this particular mutation with Osimertinib. Hence, we would like to discuss Osimertinib as a viable treatment option in EGFR Exon 18 p.Glu709_Thr710delinsAsp mutated lung adenocarcinoma.